Upregulation of an Artificial Zymogen by Proteolysis. (16th August 2016) - Liu, Zhe; Lebrun, Vincent; Kitanosono, Taku; Mallin, Hendrik; Köhler, Valentin; Häussinger, Daniel; Hilvert, Donald; Kobayashi, Shu; Ward, Thomas R.
Abstract: Regulation of enzymatic activity is vital to living organisms. Here, we report the development and the genetic optimization of an artificial zymogen requiring the action of a natural protease to upregulate its latent asymmetric transfer hydrogenase activity.